2004
DOI: 10.1002/ps.967
|View full text |Cite
|
Sign up to set email alerts
|

Influence of herbicide‐resistant canola on the environmental impact of weed management

Abstract: The growth of herbicide-resistant canola varieties increased from 10% of the canola area in Canada in 1996, when the technology was first introduced, to 80% in 2000. From 1995 to 2000, the amount of herbicide active ingredient applied per hectare of canola declined by 42.8% and the Environmental Impact (EI) per hectare, calculated using the Environmental Impact Quotient for individual herbicides and the amounts of active ingredients applied, declined 36.8%. The amount of herbicide active ingredient per hectare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 11 publications
2
75
0
Order By: Relevance
“…But the degree to which herbicide usage is altered by the adoption of herbicide-tolerant varieties is largely dependent on crop-specific production practices. For example, overall herbicide use in canola is reduced in herbicidetolerant fields versus conventional fields (Brimner et al, 2005).…”
Section: Plant Communities Associated With Herbicide-tolerant Cropsmentioning
confidence: 99%
“…But the degree to which herbicide usage is altered by the adoption of herbicide-tolerant varieties is largely dependent on crop-specific production practices. For example, overall herbicide use in canola is reduced in herbicidetolerant fields versus conventional fields (Brimner et al, 2005).…”
Section: Plant Communities Associated With Herbicide-tolerant Cropsmentioning
confidence: 99%
“…The EI was designed to provide growers and weed management practitioners with a single number that indicates the magnitude of relative risk. Despite criticism mainly due to simplicity (Dushoff et al 1994), EI has been used effectively by several researchers to compare environmental risk of different pesticides and/or production systems (Fernandez-Cornejo 1998;Edwards-Jones and Howells 2001;Ziegler et al 2002;Bues et al 2003, Lan et al 2003Brimner et al 2005). The EI can be used as a decision tool, along with herbicide efficacy, crop safety, and profit margins to identify the most advantageous weed management strategy in dry beans.…”
mentioning
confidence: 99%
“…Studies can be found to support this view [151,152], but there appear to be more studies that support a small but statistically significant reduction in herbicide use [140,[153][154][155]. Because the reduction varies between crops and regions, it is difficult to draw a general conclusion.…”
Section: Changes In Herbicide Use Due To Gmht Cropsmentioning
confidence: 99%
“…Because the reduction varies between crops and regions, it is difficult to draw a general conclusion. The adoption of GMHT varieties of oilseed rape in Canada, for example, has been associated with a reduction in the amount of herbicide used per hectare as well as a decline in the potential environmental impact of chemical weed management [153]. The average soybean herbicide application rates in the U.S., in contrast, have slightly increased by 3% since the introduction of GMHT soybean (in terms of active ingredients per acreage) [140,155].…”
Section: Changes In Herbicide Use Due To Gmht Cropsmentioning
confidence: 99%
See 1 more Smart Citation